Instalasi Penerangan Jalan Umum Berbasis Energi Terbarukan Beserta Perawatannya di Kelurahan Kalimulya, Kota Depok - Nuriskasari, Isnanda; Saputra, Yuli Mafendro Dedet Eka; Nainggolan, Benhur; Ridwan , Emir (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2024)
Kalimulya Depok Village requires a solar-powered public street lighting program. The objective of this program is not only to address the community's issue of insufficient street lighting but also to serve as an educational initiative by PNJ faculty members to enlighten the residents of Kalimulya about the utilization of solar energy as a sustainable source of electricity, aiming to achieve the village's aspiration for energy self-sufficiency. The activities encompassed in this initiative include a survey for the placement of solar street lighting poles, coordination with Kelurahan Kalimulya, system planning, installation of solar street lighting, and training for the operation and maintenance of solar street lighting systems. This endeavor has yielded positive outcomes for the partners, as evidenced by the installation of 2 solar street lighting units in RW 02 and RW 07 of Kalimulya Depok. Additionally, participants in the training program have acquired knowledge and skills related to renewable energy, expressing a high level of satisfaction